Applying an Audiobooks Application and the Literature Circle Strategy in an Online Class to Teach Reading: How? - Muhammad Fadhli (Tarling : Journal of Language Education, 2022)
The corona virus outbreak has encouraged educators to switch from face-to-face learning to online learning. This article discusses how to apply the literature circle strategy and audiobooks application in an online classroom to teach reading. This article outlines procedures for assuring interaction between students, students with learning materials, and students with lecturer in an online classroom. In addition, the advantages of using the literature circle strategy and audiobooks application are also highlighted in this article.